The forgotten members of the glucagon family - Bataille, Dominique; Dalle, Stéphane (Diabetes research and clinical practice, 2014)
From proglucagon, at least six final biologically active peptides are produced by tissue-specific post-translational processing. While glucagon and GLP-1 are the subject of permanent studies, the four others are usually left in the shadow, in spite of their large biological interest. The present review is devoted to oxyntomodulin and miniglucagon, not forgetting glicentin, although much less is known about it. Oxyntomodulin (OXM) and glicentin are regulators of gastric acid and hydromineral intestinal secretions. OXM is also deeply involved in the control of food intake and energy expenditure, properties that make this peptide a credible treatment of obesity if the question of administration is solved, as for any peptide. Miniglucagon, the C-terminal undecapeptide of glucagon which results from a secondary processing of original nature, displays properties antagonistic to that of the mother-hormone glucagon: (a) it inhibits glucose-, glucagon- and GLP-1-stimulated insulin release at sub-picomolar concentrations, (b) it reduces the in vivo insulin response to glucose with no change in glycemia, (c) it displays insulin-like properties at the cellular level using only a part of the pathway used by insulin, making it a good basis for developing a pharmacological workaround of insulin resistance.